KEEFEKTIFAN MULTIMEDIA BERBASIS KOMPUTER UNTUK PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV SD PERCOBAAN II DEPOK SLEMAN - Budyartati, Sri (Premiere Educandum, 2013)
This research aims at: (1) identifying the effecteiveness of multi media-based learning on Social Science; (2) describing the attractiveness of multi media-based learning on Social Science; which is carried out at SD Percobaan II Caturtunggal Depok Sleman Yogyakarta, term 2007/2008. The research design is pretest-posttest control group design. The data are drwan through tests which are analized quantitatively; and questionaire to measure the attractiveness of multimedia-based learning model, which will be analized qualitatavely. The treatment is carried out out by using storyboard, which is approved by experts of multimedia and teaching method. The result of the analysis shows that multi media-based learning model significantly influence the studentsâ achievement in Social Science. While the attractivemess of multi media-based learning relatively high, which is shown by 4.2 of average (in 1-5 scale measure).Â Keywords: Learning Effectiveness, Multi Media-Based Learning